PENGARUH PENYULUHAN KESEHATAN DENGAN MEDIA VIDEO TERHADAP PERILAKU PERSONAL HYGIENE PADA SISWA SD DI SEKOLAH DASAR INPRES LANRAKI 2 MAKASSAR - haikal alpin (Stikes Graha Edukasi Makassar, 2019)
The purpose of the study: to find out video media on behavior before and after personal hygiene in elementary students at the Inpres Lanraki 2 Elementary School in Makassar. Method: This study used a quasy experimental design with a design of one group pre-test and post-test with a sample of 63 respondents in class IV, V and VI students at the SD inpres Lanraki 2 Makassar. Results: The results of the study showed that of the 63 respondents surveyed there were significant influences on the pre-test and post-test. From the results of statistical tests using the Wilcoxon non parametric test with a value of p = 0,000 5 0,05. This means that H0 is rejected and Ha is accepted, so it can be concluded that there is an effect of counseling with video media on personal hygiene behavior. Discussion: Personal hygiene is an important factor because there are problems with personal hygiene that will affect one's health. Poor personal hygiene will make it easier for the body to get various diseases, such as skin diseases, infectious diseases, oral diseases, and gastrointestinal diseases or even eliminate the function of certain body parts, such as the skin. Conclusion: There is an effect of counseling with video media on personal hygiene behavior. Suggestion: It is expected that counseling on personal hygiene behavior will be one of the actions that must be improved by the teacher / teacher in the lives of students in the school environment